CHALLENGES IN IMPLEMENTING GREEN TECHNOLOGIES IN INDUSTRIAL ENTERPRISES AND SOLUTIONS - Ergashev Sanjarbek Sobirjon ugli (Scholar Express Journals, 2025)
This article explores the challenges of implementing green technologies in industrial enterprises, focusing on the ecological, economic, and organizational barriers that companies face. High initial costs, lack of awareness, technological limitations, regulatory issues, and resistance to change are identified as major obstacles. The article also presents various solutions to overcome these challenges, including government support, private sector collaboration, public awareness campaigns, and technological innovation. The adoption of green technologies is essential for promoting industrial sustainability and mitigating environmental impacts.
Keywords: Green Technologies; Industrial Sustainability